Mengenal Ibnu Qutaibah dan Kitab Ta'wil Mukhtalif Al-Hadits - Hartono, Sidiq; Nasution, Muhammad Roihan; Pulungan, Juli Julaiha (UIN Sumatera Utara Medan, 2025)
The book Ta’wil Mukhtalif al-Hadith by Ibn Qutaibah ad-Dainuri is one of the significant classical works in the field of hadith studies, particularly in addressing apparent contradictions between hadiths. Previous studies on this work have predominantly focused on its content, while the methodological framework employed by Ibn Qutaibah in composing and organizing his arguments remains underexplored. In fact, the writing methodology reflects not only the author's scholarly approach but also the intellectual context of his time. This study aims to thoroughly examine Ibn Qutaibah’s methodology in writing Ta’wil Mukhtalif al-Hadith, including the structure of the text, the pattern of argumentation, and the methods he used to reconcile conflicting hadiths. Employing a qualitative approach with library research and content analysis methods, this study uses the primary text of the book as the main source. The findings reveal that Ibn Qutaibah systematically applied several approaches: al-jamʿ (harmonization), an-naskh (abrogation), at-tarjih (preference), and at-ta’wil (interpretation) to resolve contradictions contextually. This research contributes to a deeper understanding of classical hadith scholarship and enriches the methodological discourse in hadith studies.